Bacteriological examination of the peri- and endo-dontal diseases in dogs - Kuraku, Anjali; Mulinti, Raghunath; Vaddadi, Devi Prasad; Manda, Srinivas; Tejaswi, Penugonda (Indian Journal of Veterinary Surgery, 2026)
The study was conducted on 24 clinical cases of dogs with various symptoms related to different peri- and endo-dontal affections. All the cases were evaluated by clinical examination, dental radiography, microbiological evaluation and antibiotic sensitivity testing. On microbial evaluation, bacterial culture like Staphylococcus sp. was isolated from 23 samples and Escherichia coli organisms from 11 samples. Antibiogram of the dental swabs revealed high sensitivity towards ciprofloxacin followed by doxycycline and high resistance towards metronidazole followed by clindamycin. Antimicrobial evaluation and antibiotic sensitivity testing played a major role in treatment of the periodontal and endodontal affections in dogs with good clinical outcome.